Plan estratégico para la unidad productiva agropecuaria cevallitos de la parroquia Chicaña, cantón Yantzaza, provincia de Zamora Chinchipe - Cevallos Lavanda, Mayra Narciza (2015)
The present investigation called STRATEGIC PLAN FOR AGRICULTURAL PRODUCTION UNIT CEVALLITOS, Chicano PARISH, CANTON Yantzaza, PROVINCE OF ZAMORA CHINCHIPE was carried out with the purpose of knowing the productive reality and propose strategies to improve farm production. To carry out the Plan of the estate after first diagnosis strategies and the projects were raised was performed. The results achieved are: The Cevallitos property has an area of 30 ha, of which 23.5 ha are planted pastures, 2 ha of agricultural crops and 0.5 ha of construction. Have an unproductive area of 4 ha which is mountain area. The soils of the farm are silty, clayey and fertile. The topography of the property is irregular with small areas of plain. The property has a creek with clean water for use in the house and animals. The bedroom house has electricity and treated water. Farm crops are grasses, cacao, banana, cassava, maize and papaya; animals such as cattle, pigs, chickens, guinea pigs and equine species. On the farm there is a house 4/4 serving housing for the owner. There are also buildings for animals as a Chanchera and cages for small animals. The main problems of the estate are: The owner of the farm is not trained in the administrative field, does not have a work plan for their activities and no control of work done is done. Another problem is the lack of records, making it difficult to keep accounts of expenditure and income, so it can not determine the profits of production. On the farm there technology to facilitate the activities is used, only the basic tools of agriculture which hinders the work is used. The handling of animals, is anti-technical, since it does not have a health calendar, nor a good diet is given, therefore production is low. The infrastructure of the estate is scarce, there is a barn for cattle and a shed for birds, and handling of animals 6 does paddock level. Consequence is low production and a minimum return on the farm. The main strengths of the estate are:  The farm owner is resident in the same, so there is a permanent job control. There are no debts with any financial institution in the city, so it is a subject of credit. The soils of the farm are good quality so can be undertaken in agricultural production projects. It has plenty of clean water, since the farm crossing a creek that is permanent. The farm production is given by cocoa, banana, cheese, and cheese. Bovine farm has good genetics, The main projects and activities of the plan are:  Training program in the field of administrative management of farms. Formulation Improvement Plan for the Finca, 2016-2020. Design and use of records in farm production. Training program on technical management of agricultural production. Training of the owner of the farm basics of accounting. Purchase of modern equipment for agricultural production. Renewal of fruit on the farm. Soil analysis of the estate to know its chemical composition. Renewal of grassland with improved grasses and legumes species. Evening pasture on the farm after the departure of the animals. Program control of pests and crop diseases. Planting short-cycle crops in rotation. Design and implementation of a vaccination and deworming schedule for animal species. Formulation of a supplementary ration for cattle according to their nutritional requirements. Weaning calves at 6 months of age. Playing cattle by artificial insemination. Building a barn for cattle. Nutritional formulation for swine rations. Improvement of birds and guinea pigs brood stock good genetics. There is no accounting management of resource use within the productive and administrative processes within the farm because of the lack of a trained professional. Agricultural and livestock production farm technical 7 processes are managed empirically. There are situations of disregard of the production processes of the property by the owner. The agricultural production generated on the farm only supplies household consumption of their owners. Pasture consumption by cattle being haphazardly without any specific control. Availability of water has to be used in both agricultural production areas as livestock resource. There is availability of large space of land to be used in processes of improved production. Recommendations Increase in local mitigation plans on the negative effects arising as a result of livestock production. Make appropriate use of existing resources in the farm as an alternative to boost agricultural and livestock production. Optimizing the space available, through redeployment and efficient use of existing productive areas in Cevallitos farm. Manage the support of both government institutions MAGAP, AGROCALIDAD, Provincial Council for the implementation of the proposed improvements and thus to faithfully comply with the goals previously raised